WBSN based safe lifestyle: A case study of heartrate monitoring system - Vidhyotma Gandhi; Jaiteg Singh (International Journal of Electrical and Computer Engineering (IJECE), 2020)
A Heart is the vital organ of the body. According to the “world health statistics, 2017” by WHO, about 460,000 people die due to fatal heart attacks every year. To reduce the death rate due to fatal heart attacks and malfunctioning of the cardiovascular system, this paper proposed a Wireless Body Sensor Network (WBSN) based, portable, easily affordable, miniatured, accurate “Heartrate Monitoring System (HMS)”. HMS can be used to regularly examine the cardiac condition at home or hospital to avoid or early detection of any serious condition. Heartrate Monitoring Algorithm (HMA) was designed to observe the spread heartbeat spectrum and worked at the backend of HMS. A case study was performed for forty healthy young subjects. Each subject data was computed for (sub) ̅-3S_d